Anti-cancer therapeutic potential of quinazoline based small molecules via global upregulation of miRNAs - Nahar, Smita; Bose, Debojit; Panja, Sumit Kumar; Saha, Satyen; Maiti, Souvik (Chemical Communications, 2014)
Three quinazoline based small molecules showed global upregulation of miRNA expression with a selective enrichment of tumor suppressor miRNAs. The target genes of the upregulated miRNAs were predicted to be enriched for apoptotic pathways. Apoptotic induction following treatment with quinazoline compounds was confirmed by in cellulo studies. Thus, these small molecules having the core structural moiety (2,4-diphenyl-quinazoline) can be used as scaffolds to design activators of miRNA expression paving the way for novel anti-cancer drugs.